Strategic marketing plan in achieving marketing values and objectives at Mitha Pre-Marriage Healthcare and Aesthetic Clinic - Hannak, Nasriyatul; Kustiawan, Unggul; Indradewa, Rian; Dhafi Iskandar, Muhammad (International Journal of Applied Finance and Business Studies, 2024)
Klinik Mitha is a business entity in the form of a Limited Liability Company (PT) in the field of health services in accordance with the definition referred to in 1 Permenkes No 028/2011 and the estimate required for the stages until it becomes a PT is 1 month until the notarial deed. Marketing plan is a planning process in the field of marketing in order to achieve the marketing targets that have been set. In marketing planning is closely related to marketing strategies that concern the values and goals of the company. In this chapter, Mitha Clinic will focus on Marketing Goals and Objectives, STP Strategy that will be carried out, B2C Marketing Mix, Sales activities, Sales Budget Projections and Revenue Stream projections. The purpose of this research is for a Clinic known to the DKI Jakarta Community for reputable premarital and aesthetic health services, Customer Satisfaction by Optimizing Premarital and Aesthetic Health Services and in the long term can build new branch clinics again. The results of this study indicate that the marketing plan strategy in achieving value and marketing goals is influenced by several factors such as the purpose of establishing the business, marketing planning which includes price, location, promotion, sales, and planning in finance.